Obstacles in Applying Local Wisdom to the Government of the Sultanate of Buton in Realizing a Democratic Baubau City Government - Rizki Mustika Suhartono; Ernawati Ernawati (Jurnal Hukum Volkgeist, 2021)
This research was conducted to know the cultural influence of the Sultanate of Buton in realizing a democratic Baubau City. This research uses normative research that uses library data or legal materials that are primary and secondary legal materials and tertiary legal materials. Obstacles in applying local wisdom of the government of the Sultanate of Buton in realizing a democratic Baubau City government, namely the tendency of materialism, individualism, elitism and secularism. It is recommended that the cultural values of the people contained in the Binci-binciki Kuli Philosophy (pinch each other will feel the same pain), which includes the principles of equality, equality and justice must be understood, internalized, and applied by all communities who support these values to realize the democratic autonomous regional government of Baubau.